Antimetastasis gene expression and numerical chromosomal abnormalities of chromosomes 1 & 17 in serous tumours of the ovary - (:unkn) unknown (I R O G CANADA, INC, 2001)
Objective(s): The aim of this study was to examine the expression of the antimetastasis gene nm23 and numerical changes on chromosome 1 and 17 in ovarian tumours. Methods: In this study 20 serous cystadenocarcinomas, ten borderline and five benign tumours were analysed for expression of the nm23 antimetastasis gene by immunohistochemistry and for numerical chromosomal abnormalities of chromosomes I and 17 by interphase cytogenetics. Results: Strong intracytoplasmic immunoreactivity with the antimetastasis gene was observed in late stage carcinomas but not in benign or borderline tumours or in lymph node metastases. Numerical abnormalities were only observed in carcinomas. Conclusion(s): These sets of data are consistent with the majority of benign and borderline tumours lacking invasive potential. Odds Ratio (OR) assessment indicates that the presence of numerical aberrations correlates with immunopositivity.
Keywords: nm23 expression; interphase cytogenetics; ovarian tumours; NM23 EXPRESSION; METASTASIS; CARCINOMA; TUMORS